Follicular thyroid carcinoma metastatic to skin: a small papule and a big diagnostic change - Marcia Lanzoni Alvarenga Lira; Mariana Abdo de Almeida; Michele Maria Reis-Feroldi; Jeanine Alvarenga Rocha (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Cutaneous metastases are uncommon in daily practice, although very important, since they may be the first manifestation of an undiscovered primary neoplasm or the first indication of recurrence. Cutaneous metastases from the breast are the most frequent in women and cutaneous metastases from the lung are the most frequent in men. Thyroid carcinoma, despite representing the most frequent endocrine neoplasm, is considered a rare neoplasm, corresponding to 1% of malignant neoplasms diagnosed. Cutaneous metastases from follicular carcinoma are rare and occur mainly in the head and neck area. We report a case of cutaneous metastasis in a patient with follicular thyroid carcinoma and breast carcinoma. Because of the association of these two neoplasms, the possibility of Cowden Syndrome - multiple hamartoma syndrome - was raised, but was excluded by genetic analysis of PTEN gene.